Comparison of surgical wound infection and dehiscence following the use of two methods of nylon sutures and skin staples in staples in diabetic mellitus patients undergoing total knee arthroplasty surgery: a randomized clinical trial study - Haadiyeh Rahbari; Mohammadamin Ahmadi; Mina Amiri Doreh; Samira Mahmoudi; Parvin Ghaemmaghami; Armin Fereidouni (BMC Musculoskeletal Disorders)
Abstract Objective Timely and complete surgical wound healing substantially affects the patient’s performance and satisfaction with surgery outcomes. Sutures and staples are two common wound closure methods in total knee arthroplasty; however, their role in reducing the rate of surgical wound infections and dehiscence in diabetic patients is unclear. Therefore, this study was conducted to investigate the rate of infection and post-closure dehiscence in wounds closed with either nylon sutures or skin staples in diabetic patients undergoing total knee arthroplasty (TKA). Methods This is a single-blind randomized clinical trial including 70 diabetic mellitus patients undergoing TKA. Patients were selected using a restricted random sampling method and haphazardly assigned to study groups using the permuted block randomization technique, including the suture-closed (n = 35) and staple-closed (n = 35) groups. The follow-up was 2 to 8 weeks after the surgery, evaluation of wound infection and dehiscence was performed. Results The present study showed that there was no significant correlation between wound infection rate (P-value = 0.254) and wound dehiscence (P-value = 0.324) with the method of wound closure (i.e., sutures or staples). However, surgical wound dehiscence revealed a significant correlation with body mass index (BMI) (P-value = 0.044), Glycosylated hemoglobin (HbA1c) (P-Value = 0.001), and fasting blood glucose (FBS) (P-Value = 0.012) in diabetic mellitus patients. Conclusion The use of the staple technique compared to suture had no difference in the rate of wound opening and infection, but from a clinical point of view, the prevalence of wound opening after TKA in patients with the suture method was higher than that of staples. Further research is needed to confirm these findings and the long-term efficacy of each method. Clinical trial registration The present study was registered at the Iranian Registry of Clinical Trails (No. IRCT20230928059543N1, Trial Id:74754, approved on 12/01/2024, https://irct.behdasht.gov.ir/user/trial/74754/view ) and conducted according to Consolidated Standards of Reporting Trials (CONSORT) guidelines.